2015
DOI: 10.4253/wjge.v7.i4.403
|View full text |Cite
|
Sign up to set email alerts
|

Re-bleeding events in patients with obscure gastrointestinal bleeding after negative capsule endoscopy

Abstract: Patients with OGIB despite a negative capsule endoscopy have a significant re-bleeding risk; therefore, these patients require an extended follow-up strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
5
20
1
Order By: Relevance
“…Remarkably, the majority of re-bleeding episodes (81.3%) occurred within the first 2 years after VCE examination, while the cumulative risk of re-bleeding raised from 12.9% at 1, to 25.6% at 3 and to 31.5% at 5 years, respectively (31); this finding being verified by other authors (29). In keeping with the findings of previous reports (25,32), the median time until first rebleeding event was 15 months, underlying the value of patient monitoring for at least the first 2 years post negative VCE exam and perhaps later on, as the interquartile range for the time lag to re-bleeding was between 2 and 33 months (31).…”
Section: Re-bleeding Rate After Index Vce Small Bowel Examinationsupporting
confidence: 79%
See 3 more Smart Citations
“…Remarkably, the majority of re-bleeding episodes (81.3%) occurred within the first 2 years after VCE examination, while the cumulative risk of re-bleeding raised from 12.9% at 1, to 25.6% at 3 and to 31.5% at 5 years, respectively (31); this finding being verified by other authors (29). In keeping with the findings of previous reports (25,32), the median time until first rebleeding event was 15 months, underlying the value of patient monitoring for at least the first 2 years post negative VCE exam and perhaps later on, as the interquartile range for the time lag to re-bleeding was between 2 and 33 months (31).…”
Section: Re-bleeding Rate After Index Vce Small Bowel Examinationsupporting
confidence: 79%
“…In the study by Min et al (37), 66/116 patients who discontinued anticoagulant medication after VCE demonstrated lower re-bleeding rate; interestingly, use of anticoagulants before and after VCE was not associated with re-bleeding, overall. Similar to previous reports, Cúrdia Gonçalves et al (62) found only marginal association between anticoagulants use and re-bleeding episode, while another study identified anticoagulant use as predictor of future re-bleeding events (HR: 3.9; 95% CI, 1.5-9.9; P=0.004) (31). However, since all these studies were powered only for the primary endpoint and investigation for predictors of re-bleeding were regarded merely a secondary one, the possibility of a type II error cannot be excluded.…”
Section: Predictive Factors For Re-bleeding After Index Vcesupporting
confidence: 75%
See 2 more Smart Citations
“…In the CKD cohort, the sensitivity was 88.9%, compared to the 30% sensitivity of colonoscopy [62] Docherty et al, 2015 Assessed the diagnostic yield of VCE in evaluating OGIB in patients with CKD. 51% had findings on VCE, and 33.3% had angiodysplasia as the cause of bleeding [35] Magalhaes-Costa et al, 2015 Evaluated the rate of recurrent OGIB after a negative VCE and found that patients with CKD had an increased HR of 3.498 for re-bleeding on univariate analysis (95% CI=1.265-9.671, P=0.016) [52] without active bleeding (92.3% vs. 12.9%). In those with prior episodes, the earlier the VCE was done after the cessation of bleeding, the higher the yield [33].…”
Section: Vcementioning
confidence: 99%